Wang Lee-hom to star as Stan Lee's Annihilator. - Tseng, Ada (Asia Pacific Arts, 2013)
The article focuses on the selection of Wang Leehom as the leading actor for adaptation of Stan Lee's film "Annihilator." It mentions the name of the crew members of the film including producer Barry Josephson and screenwriter Dan Gilroy. It also discusses Leehom's performances in several films of director Ang Lee including "Lust," "Caution" and "Little Big Soldier."